The Influence of the Pedagogical Competence of History Teachers on Student Activities and Learning Outcomes in Class X History Subjects - Muaini, Muaini; Rosada, Rosada; Salman, Salman (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
This study aims to determine the effect of pedagogical competence of history teachers on activities and learning outcomes in class X history subjects at MAN 3 Mataram City. This study uses quantitative research with a quantitative descriptive approach. The population and samples used were 30 students. Data collection using Pre Test and Post Test instruments in the form of a questionnaire (questionnaire) of pedagogical competence of history teachers and student learning activities using questionnaires and student learning outcomes using student end-of-semester assessment test scores. The results of the research obtained that, by making a value decision, if the significant value> 0.05, it means that variable X has no effect on variables Y1 and Y2, and if the significance value <0.05, it means that there is an influence of variable X on variables Y1 and Y2. From the results of the simple linear regression test that has been carried out, the significance value obtained for variable X on Y1 is (0.001) and variable X on Y2 is (0.003), which means it is smaller than 0.05. So it can be concluded that seen from the basis of the T test decision making, namely, if the significance value <0.05, then Ha is accepted, which means that there is an influence of variable X on variables Y1 and Y2. In other words, there is an effect of the influence of the pedagogical competence of history teachers on activities and learning outcomes in class X history subjects.